Developing an interactive e-book integrating pedagogical deep learning and local wisdom to enhance digital literacy and mathematical critical thinking - Irena Puji Luritawaty; Edi Supriyadi; Ekasatya Aldila Afriansyah; Dian Mardiani (Jurnal Elemen, 2026)
This study aimed to develop and evaluate an interactive e-book integrating deep learning principles with Garut local wisdom to enhance digital literacy and mathematical critical thinking. Using a research and development (R&D) approach with the ADDIE model and a quasi-experimental design, 73 seventh-grade students participated: 36 in the experimental group and 37 in the control group. Data were collected through mathematical critical thinking tests, digital literacy questionnaires, and expert validation sheets, then analyzed using normalized gain scores, the Mann-Whitney U test, and Cohen’s d. The e-book achieved very high validity (93.33%) and practicality ratings exceeding 95%. The experimental group demonstrated significantly greater gains in mathematical critical thinking (Ng = 0.89) than the control group (Ng = 0.70), with a Cohen’s d of 2.59 indicating a very strong effect. Additionally, 95.35% of students reported improved digital literacy. These findings indicate that culturally grounded interactive e-books can effectively enhance 21st-century skills, providing a replicable framework for integrating local wisdom in mathematics education across diverse cultural contexts.